Congenital myasthenic syndromes. - Beeson, D; Palace, J; Vincent, A (1997)
Congenital myasthenic syndromes are a rare group of heterogeneous disorders affecting neuromuscular transmission. Recent identification and in-vitro functional analysis of some of the genetic mutations that cause these disorders correlates with previous electrophysiological, biochemical, pathological and therapeutic studies, and has advanced our understanding of neuromuscular transmission.